2016
DOI: 10.1371/journal.pone.0159509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Evolution of Hepatitis B Virus Genotypes in Symptomatic Acute Infections in Argentina

Abstract: Hepatitis B virus (HBV) is a globally distributed human pathogen that leads to both self-limited and chronic infections. At least eight genotypes (A-H) with distinct geographical allocations and phylodynamic behaviors have been described. They differ substantially in many virological and probably some clinical parameters. The aim of this study was to analyze full-length HBV genome sequences from individuals with symptomatic acute HBV infections using phylogenetic and coalescent methods. The phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…In Argentina, it has been recently reported a high prevalence of sgtF1b in acute and chronic HBeAg positive infections followed by sgtA2, sgtF4 and sgtD. [ 13 15 ] Our results showed the same relative fitness between all of the genotype combinations, with the exception of the pair F1b-F4, which showed an increase of sgtF1b in the progeny. Additionally, when serial cycles of infection were simulated, results showed that the ratio between F1b and F4 kept moving in the direction of F1b predominance.…”
Section: Discussionsupporting
confidence: 63%
“…In Argentina, it has been recently reported a high prevalence of sgtF1b in acute and chronic HBeAg positive infections followed by sgtA2, sgtF4 and sgtD. [ 13 15 ] Our results showed the same relative fitness between all of the genotype combinations, with the exception of the pair F1b-F4, which showed an increase of sgtF1b in the progeny. Additionally, when serial cycles of infection were simulated, results showed that the ratio between F1b and F4 kept moving in the direction of F1b predominance.…”
Section: Discussionsupporting
confidence: 63%
“…However, in this study, subgenotype F1b was notably present in 57% of the native cases (NOaxaca and NMichoacan) showing a closely genetic relatedness with other Latin American F1b strains. Other than the F1b cluster recently reported in Italy, this subgenotype that is more common among the western South American countries of Argentina and Chile has also been found in natives of Colombia and in Venezuela . Despite that HBV genotype H is most predominant in native Mexicans, the F1b strains found in Oaxaca were isolated from descendants of the ancient Mesoamerican Mixtecos.…”
Section: Discussionmentioning
confidence: 68%
“…The main reasons are the stratification of the population structure comprised of Native Amerindians and genetically-admixed Mestizos (Amerindian, Caucasian, and African lineages) and the concurrent high level of economic inequality. 12 Thereby, the endemic genotype H in Mexico 13 and the F1-F4 subgenotypes of Central and South America [14][15][16][17] correspondingly circulate among natives, rural, or urban, low-income class Mestizo subpopulations. Likewise, genotypes A, D, or B, C that circulate among urban populations of European descendants and Asian immigrants, respectively have been related to liver damage.…”
mentioning
confidence: 99%
“…In this study, we report evidence of an incomplete autophagy process induced by HBV sgts F1b and F4 replication in Huh-7 cells. These sgts, native from Latin America, are responsible for most of the new acute and chronic infections in our country [ 8 , 10 ], and have been scarcely studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals infected with HBV sgt F1b seroconvert e antigen (HBeAg) later in life than those infected with sgt F4 [ 8 ]. In addition, recent studies have shown that sgt F1b is the main responsible of the new acute and chronic infections in Argentina [ 8 10 ]. Moreover, growing evidence has shown a close association of sgt F1b with more severe course of chronic HBV infections, and a high correlation between sgt F1b and the development of HCC exists among Alaska native people [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%